A study of evening convective clouds over Kochi and neighbourhood - MATHEW, A. J.; KAIMAL, S. U. (MAUSAM, 2001)
Radar echoes of 0900 and 1100 UTC over Kochi and 200 km around were studied from 1996 to 1999 along with SST of southeast Arabian Sea and Kochi. The following results are obtained : Monsoon convective cloud tops were lower than Pre-monsoon and Post-monsoon convective cloud tops. (ii) In the mean, monsoon cloud tops gradually increased from 1996 to 1998 and then decreased. (iii) Very large convective activity existed during August 1997 to June 1998 compared to other periods of this study. Seasonally the higher the SST, the higher is convective cloud top. (v) Interannually, large positive SST anomaly coincided with high convective activity and this may be related to then prevailing El Nino.